2016
DOI: 10.1007/s12288-016-0680-0
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Reticulocyte Parameters for Diagnosis of Hereditary Spherocytosis in Children

Abstract: Innovations in laboratory equipment have enabled a widening of the spectrum of hematological parameters obtained from single measurements of peripheral blood samples, including reticulocyte parameters. The usefulness of reticulocytes indices to confirm the diagnosis of pediatric anemia was analyzed in this study. The study group consisted of 163 children, aged 1 month-17 years, with anemia. Complete blood count extended with an analysis of reticulocyte parameters were measured using a Beckman Coulter LH 750. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 31 publications
2
8
0
Order By: Relevance
“…Similar observations were made by Ciepiela O et al 8 in their study in which the RBC size factor was found to be low in patients with HS. Since the calculation of Rsf is based MSCV is another parameter which has been studied by few authors and have been proved to have high sensitivity and specificity in screening of HS.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similar observations were made by Ciepiela O et al 8 in their study in which the RBC size factor was found to be low in patients with HS. Since the calculation of Rsf is based MSCV is another parameter which has been studied by few authors and have been proved to have high sensitivity and specificity in screening of HS.…”
Section: Discussionsupporting
confidence: 90%
“…From the different reticulocyte parameters which were analyzed, area under the curve was calculated for IRF, MRV and Retic#/IRF which was 0.867, 0.865 and 0.931 respectively. Ciepiela O et al, 8 in their study derived AUC for MRV which was 0.963 with a sensitivity of 87.66% and specificity of 94.12%., at a cut off value of 91.15fl. AUC for reticulocyte parameters were also calculated by Lazarova E et al The AUC for MRV, IRF and Retic#/IRF were 0.98, 0.50 and 0.95 respectively from which they derived cut off values of <96.7, >0.19 and >1.5 respectively.…”
Section: Discussionmentioning
confidence: 92%
“…Low MSCV has been demonstrated to be a sensitive parameter for HS detection (20). When expressed as delta MSCV, i.e., the difference between MCV and MSCV (MCV-MSCV), this measurement has even higher discriminatory value for the detection of HS, which is confirmed by increased delta MSCV (19,(21)(22)(23).…”
Section: Complete Blood Count (Cbc) Analysismentioning
confidence: 93%
“…Patients with HS present a high reticulocyte count with a low immature reticulocyte fraction (IRF). These less mature reticulocytes are recognized as cells with higher RNA levels (21). Mullier et al showed that mild cases of HS have a Ret/IRF ratio higher than 19, while severe cases of HS have a Ret/IRF ratio higher than 7.7 (15).…”
Section: Complete Blood Count (Cbc) Analysismentioning
confidence: 99%
See 1 more Smart Citation